Hypophosphatasia: Enzyme Replacement Therapy Brings New Opportunities and New Challenges. (31st January 2017) - Whyte, Michael P
ABSTRACT: Hypophosphatasia (HPP) is caused by loss‐of‐function mutation(s) of the gene that encodes the tissue‐nonspecific isoenzyme of alkaline phosphatase (TNSALP). Autosomal inheritance (dominant or recessive) from among more than 300 predominantly missense defects of TNSALP (ALPL) explains HPP's broad‐ranging severity, the greatest of all skeletal diseases. In health, TNSALP is linked to cell surfaces and richly expressed in the skeleton and developing teeth. In HPP, TNSALP substrates accumulate extracellularly, including inorganic pyrophosphate (PPi), an inhibitor of mineralization. The PPi excess can cause tooth loss, rickets or osteomalacia, calcific arthropathies, and perhaps muscle weakness. Severely affected infants may seize from insufficient hydrolysis of pyridoxal 5ʹ‐phosphate (PLP), the major extracellular vitamin B6 . Now, significant successes are documented for newborns, infants, and children severely affected by HPP given asfotase alfa, a hydroxyapatite‐targeted recombinant TNSALP. Since fall 2015, this biologic is approved by regulatory agencies multinationally typically for pediatric‐onset HPP. Safe and effective treatment is now possible for this last rickets to have a medical therapy, but a number of challenges involving diagnosis, understanding prognosis, and providing this treatment are reviewed herein. © 2017 American Society for Bone and Mineral Research.